Analisis Komparatif Kinerja Puskesmas Denpasar Selatan dan Denpasar Timur Dengan Menggunakan Metode Balaced Scorecard - Mahardika, Ketut; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2014)
Health centers are the top of public health services in Indonesia. With the health centers, each people can get health care easily and affordable. In the past, health center performance is more often focused on customer satisfaction or patient. This study is a descriptive comparative study aimed to determine and compare the performance of health centers in south and east Denpasar using the balanced scorecard method. The health centers in south and east Denpasar chosen as the study site because the health centers in the two districts are already implementing a quality management system in accordance with Health Department standards and there is a health center that operates 24 hours in each. The study used primary data obtained from the answers given by the respondents and using secondary data from health centers financial data. Variables examined include the performance of the financial perspective, customer perspective, internal business processes, and learning and growth perspective.
Keywords: Balanced Scorecard, Performance, Puskesmas